Limited Role of the Apparent Diffusion Coefficient (ADC) for Tumor Grade and Overall Survival in Resectable Pancreatic Ductal Adenocarcinoma - Deniece M. Riviere; Marnix C. Maas; Lodewijk A. A. Brosens; Martijn W. J. Stommel; Cornelis J. H. M. van Laarhoven; John J. Hermans (Diagnostics, 2024)
This study evaluated the relationship between apparent diffusion coefficient (ADC) values in pancreatic ductal adenocarcinoma (PDAC) and tumor grades based on WHO, Adsay, and Kalimuthu classifications, using whole-mount pancreatectomy specimens. If glandular formation plays a key role in the degree of diffusion restriction, diffusion-weighted imaging could facilitate non-invasive grading of PDAC. A freehand region of interest (ROI) was drawn along tumor borders on the preoperative ADC map in each tumor-containing slice. Resection specimens were retrospectively graded according to WHO, Adsay, and Kalimuthu classifications and correlated with overall survival and the 10th percentile of whole-volume ADC values. Findings from 40 patients (23 male, median age 67) showed no correlation between ADC p10 values and WHO differentiation (p = 0.050), Adsay grade (p = 0.955), or Kalimuthu patterns (p = 0.117). There was no association between ADC p10 and overall survival (p = 0.082) and other clinicopathological variables. Survival was significantly lower for poor tumor differentiation (p = 0.046) and non-glandular Kalimuthu patterns (p = 0.016) and there was a trend towards inferior survival for Adsay G3 (p = 0.090) after correction for age, tumor location, and stage. Preoperative ADC measurements for determining PDAC aggressiveness had limited clinical utility, as there was no correlation with histological parameters or overall survival in resectable PDAC.